2003
DOI: 10.1046/j.1365-313x.2003.01839.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of root transporters reveals participation of multiple gene families in the response to cation stress

Abstract: SummaryPlant nutrition critically depends on the activity of membrane transporters that translocate minerals from the soil into the plant and are responsible for their intra-and intercellular distribution. Most plant membrane transporters are encoded by multigene families whose members often exhibit overlapping expression patterns and a high degree of sequence homology. Furthermore, many inorganic nutrients are transported by more than one transporter family. These considerations, coupled with a large number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
196
1
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 282 publications
(215 citation statements)
references
References 78 publications
13
196
1
5
Order By: Relevance
“…What is the relationship of mineral elements (in particular, K + Na + in soils) with root signal transduction (pathways)? Much of former study showed that K + was little connected with anti-drought, but recent research and our results displayed that it was linked with wheat resistance drought [3,7,39,60,66,67,75]. What is the exact soil water stress threshold of individual wheat genotype?…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…What is the relationship of mineral elements (in particular, K + Na + in soils) with root signal transduction (pathways)? Much of former study showed that K + was little connected with anti-drought, but recent research and our results displayed that it was linked with wheat resistance drought [3,7,39,60,66,67,75]. What is the exact soil water stress threshold of individual wheat genotype?…”
Section: Discussionmentioning
confidence: 78%
“…Just 1 year ago, European Commission, who once kept conservative to biotechnological breeding, constructed a big project: Plants for the Future: a European vision for Plant Biotechnology towards 2025, in which much is involved in resistance drought [14]. Many advances in relation to this hot topic, including molecular mechanism of anti-drought and corresponding molecular breeding have taken place [28,33,34,39,44,47,50,53,[55][56]63,[72][73][74][75]78]. Although the obtained transgenic crops (mainly, wheat) by different types of gene technology all exhibit drought resistance to some extent, they have many shortfalls related to agronomical performance and/or development [47,49,53,62,66,68,74].…”
Section: Introductionmentioning
confidence: 99%
“…What is the relationship of mineral elements (in particular, K + Na + ) with root signal transduction (pathways)? Much of former study showed that K + was little connected with anti-drought, but recent research and our results displayed that it was linked with wheat resistance drought [8,22,49,46,42,55]. What is the exact soil water stress threshold of individual wheat genotype?…”
Section: Discussionmentioning
confidence: 79%
“…Drought is a complex physical-chemical process, in which many biological macromolecules and small molecules are involved, such as nucleic acids (DNA, RNA, microRNA), proteins, carbohydrates, lipids, hormones, ions, free radicals, mineral elements [3,8,12,13,18,20,22,26,31,43,49,50,55,65]. In addition, drought is also related to salt stress, cold stress, high temperature stress, acid stress, alkaline stress, pathological reactions, senescence, growth, development, cell cycle, UV-B damage, wounding, embryogenesis, flowering, signal transduction and so on [16,17,[26][27][28]36,37,[44][45][46][47][52][53][54]62].…”
Section: Introductionmentioning
confidence: 99%
“…K + -uptake and its re-distribution within the plant is facilitated by a plethora of membrane transport proteins displaying an astonishing diversity with respect to their affinity and selectivity for K + , mode and direction of transport, tissue specific expression, membrane localization and regulation [2]. Microarray experiments have shown that -in contrast to transporters of other macronutrients -genes encoding K + -transporters display surprisingly little responsiveness to the external nutrient supply [3]. This observation probably reflects that because of its vital role in maintenance of cell turgor and membrane potential K + -transport has to respond very quickly to changes in the environment.…”
mentioning
confidence: 99%